The Protective Role of the Carbohydrate Response Element Binding Protein in the Liver: The Metabolite Perspective - Agius, Loranne; Chachra, Shruti S.; Ford, Brian E. (Frontiers in Endocrinology, 2020)
The Carbohydrate response element binding protein, ChREBP encoded by the MLXIPL gene, is a transcription factor that is expressed at high levels in the liver and has a prominent function during consumption of high-carbohydrate diets. ChREBP is activated by raised cellular levels of phosphate ester intermediates of glycolysis, gluconeogenesis and the pentose phosphate pathway. Its target genes include a wide range of enzymes and regulatory proteins, including G6pc, Gckr, Pklr, Prkaa1,2 and enzymes of lipogenesis. ChREBP activation cumulatively promotes increased disposal of phosphate ester intermediates to glucose, via glucose 6-phosphatase or to pyruvate via glycolysis with further metabolism by lipogenesis. Dietary fructose is metabolised in both the intestine and the liver and is more lipogenic than glucose. It also induces greater elevation in phosphate ester intermediates than glucose, and at high concentrations causes transient depletion of inorganic phosphate, compromised ATP homeostasis and degradation of adenine nucleotides to uric acid. ChREBP deficiency predisposes to fructose intolerance and compromised cellular phosphate ester and ATP homeostasis and thereby markedly aggravates the changes in metabolite levels caused by dietary fructose. The recent evidence that high fructose intake causes more severe hepatocyte damage in ChREBP-deficient models confirms the crucial protective role for ChREBP in maintaining intracellular phosphate homeostasis. The improved ATP homeostasis in hepatocytes isolated from mice after chronic activation of ChREBP with a glucokinase activator supports the role of ChREBP in the control of intracellular homeostasis. It is hypothesized that drugs that activate ChREBP confer a protective role in the liver particularly in compromised metabolic states.